Wrenched from the land : activists inspired by Edward Abbey - Lincoln, M. L.; Lincoln, M. L.; Rapaport, Diane Sward; McKibben, Bill (University of New Mexico Press, 2020)
Wrenched from the Land features sixteen interviews with some of the most iconic eco-warriors to put themselves on the line for their beliefs. The activists featured in this book are inspired by the late Edward Abbey, one of America's uncompromising and irascible defenders of wilderness. The book includes interviews with Terry Tempest Williams, the late Charles Bowden, Sea Shepherd Society founder Paul Watson, Jack Loeffler, Doug Peacock, Ingrid Eisenstadter, John De Puy, Bob Lippman, Derrick Jensen, Shonto Begay, Ken Sanders, Ken Sleight, the late Katie Lee, Executive Director of the Center for Biological Diversity Kieran Suckling, Earth First! cofounder Dave Foreman, and climate activist Tim DeChristopher.